The Incompleteness of the Economy and Business: A Forceful Reminder - Dembinski, Paul H. (2011)
Many different but related arguments developed in the Caritas in Veritate converge on one central, yet not clearly stated, conclusion or thesis: economic and business activities are ‘incomplete’. This article will explore the above-mentioned ‘incompleteness’ thesis or argument from three different perspectives: the role, the practice and the purpose of economic and business activities in contemporary societies. In doing so, the paper will heavily draw on questions and, still not fully learned, lessons derived from the present financial and economic crisis. Caritas in Veritate provides an appealing moral framework in which many of these lessons take a deeper sense and a more comprehensive meaning. The notion of ‘incompleteness’ is applied here to economic and business theory and practice in the sense derived from Gödel’s theorems. They state in terms of logical and mathematical demonstrations that no system of axiomatic statements can provide a proof of its own consistency. Such a proof requires the use of statements belonging to another (higher) level system. In the case of economics or business theory and practice these ‘higher level’ statements are value judgments. By stressing the importance of ethics and moral philosophy for daily life, Caritas in Veritate strongly reminds us that neither economy nor business are self-sufficient either in organisational and social, practical or moral terms.
Keywords: Transaction; System of National Accounts (SNA); Relation; purpose of business; Incompleteness in economics; Gödel’s Theorems; Financial Crisis; Exchange; Ethics; Caritas in Veritate